(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
The list of the loculoascomycetes of the Botanical garden of Kherson State University is presented. The 28 species 20 genera 13 families 3 orders from class Dothideomycetes were founded. Taxonomical structure, ecological and throphic features of the fungi are considered.